Stenotrophomonas maltophilia, Bakteri Resisten Merkuri pada Limbah Pertambangan Logam - Gultom, Mangihot Tua; Shienen Sisilia; Mariana Wahjudi (Keluwih: Jurnal Sains dan Teknologi, 2022)
Abstract—Mercuric-resistant bacterium isolate coded 22 was previously obtained from metal mining (tailing) wastewater samples. From the total 24 bacteria which had been isolated, isolate 22 exhibited the highest resistance toward high concentration of Hg. In this paper it is reported results of 16S rDNA-based identification of isolate 22 as well as its growth and resistance characteristics when growing on Mercuric containing Nutrient Broth medium. Isolate 22 is closely related to the bacterium, Stenotrophomonas maltophilia (identity 99% and query covered 90%). Isolate 22 grew very well in the NB-Hg medium containing Hg concentration of 50 and 100 ppm. Increasing Hg concentration clearly lengthened lag phase although cell quantity (culture turbidity, OD600) at the initial phase were the same. Keywords: isolate22, Hg, identification, sequencing, 16S rRNA gene Abstrak—Isolat 22 adalah kode isolat bakteri resisten logam Merkuri (Hg) yang didapatkan pada sampel air limbah pertambangan logam (tailing). Isolat 22 adalah isolat yang paling berdaya tahan tinggi terhadap Hg, dari total 24 isolat yang berhasil diisolasi. Pada paper ini akan dilaporkan hasil identifikasi spesies bakteri isolat 22 menggunakan teknik PCR - sekuensing gen 16S rRNA dan karakter pertumbuhan dan resistensi isolat 22 terhadap Hg. Dari hasil sekuensing 16S rRNA, diketahui bahwa isolat 22 sangat dekat kekerabatannya dengan spesies Stenotrophomonas maltophilia (identity 99% dan query covered 90%). Isolat 22 tumbuh dengan baik pada medium NB-Hg dengan kadar Hg 50 dan 100 ppm. Semakin tinggi kadar Hg dalam medum, semakin lama fase lag, walaupun jumlah sel pada medium di fase awal sama. Kata kunci: isolat 22, hg, identifikasi, sekuensing, gen 16S rRNA